Exacerbation of Cushing's syndrome during pregnancy: stimulation of a cortisol-secreting adrenocortical adenoma by ACTH originating from the foeto-placental unit. (7th February 2019) - St-Jean, Matthieu; MacKenzie-Feder, Jessica; Bourdeau, Isabelle; Lacroix, André
Summary: A 29-year-old G4A3 woman presented at 25 weeks of pregnancy with progressive signs of Cushing's syndrome (CS), gestational diabetes requiring insulin and hypertension. A 3.4 × 3.3 cm right adrenal adenoma was identified during abdominal ultrasound imaging for nephrolithiasis. Investigation revealed elevated levels of plasma cortisol, 24 h urinary free cortisol (UFC) and late-night salivary cortisol (LNSC). Serum ACTH levels were not fully suppressed (4 and 5 pmol/L ( N : 2–11)). One month post-partum, CS regressed, 24-h UFC had normalised while ACTH levels were now less than 2 pmol/L; however, dexamethasone failed to suppress cortisol levels. Tests performed in vivo 6 weeks post-partum to identify aberrant hormone receptors showed no cortisol stimulation by various tests (including 300 IU hLH i.v.) except after administration of 250 µg i.v. Cosyntropin 1–24. Right adrenalectomy demonstrated an adrenocortical adenoma and atrophy of adjacent cortex. Quantitative RT-PCR analysis of the adenoma revealed the presence of ACTH (MC2) receptor mRNA, while LHCG receptor mRNA was almost undetectable. This case reveals that CS exacerbation in the context of pregnancy can result from the placental-derived ACTH stimulation of MC2 receptors on the adrenocortical adenoma. Possible contribution of other placental-derived factors such as oestrogens, CRH or CRH-like peptides cannot be ruled out. Learning points: Diagnosis of Cushing's syndrome during pregnancy is complicated by several physiological alterations in hypothalamic–pituitary–adrenal axis regulation occurring in normal pregnancy. Cushing's syndrome (CS) exacerbation during pregnancy can be associated with aberrant expression of LHCG receptor on primary adrenocortical tumour or hyperplasia in some cases, but not in this patient. Placental-derived ACTH, which is not subject to glucocorticoid negative feedback, stimulated cortisol secretion from this adrenal adenoma causing transient CS exacerbation during pregnancy. Following delivery and tumour removal, suppression of HPA axis can require several months to recover and requires glucocorticoid replacement therapy.